A new species of Pristimantis (Amphibia: Craugastoridae) with cranial crests from the Colombian Andes - Ospina-Sarria, Jhon Jairo; Mendez-Narvaez, Javier; Burbano-Yandi, Carlos; Bolívar-G, Wilmar (Zootaxa, 2011)
We describe a new species of Pristimantis (Anura: Craugastoridae) from Reserva Natural “La Sirena”, Valle del Cauca, Colombia. The new species is found in the Cordillera Central and is similar to P. calcaratus, P. kelephus and P. jubatus, all of them found in the Cordillera Occidental and are presumed to be related. The new species is distinguished from similar species by having cranial crests, tip of Toe V reaching the distal subarticular tubercle of Toe IV, conical tubercles present on heels and interocular area, and males lacking vocal slits but having white, glandular nuptial pads on thumbs.